(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Criminology has become in-demand in schools and universities, not because of the bearing appearance that attracts the youth to enroll in, but because of the moral attitude and other forms of showing respect to their other upper-class men and professors. The variety of opportunities that await after the accomplishment of the degree. The criminology department has its own rules and regulations that must followed, such as giving respect, hand gestures, salutes, sidestepping, and proper greetings to their upper-class men and professors; they must obey the command as their job as cadets, as well as proper haircut and uniform. Some students violate this, thinking they forgot or they cannot recognize their seniors; they ought to follow orders while studying, and they will carry on until they have a profession. The usual problem is the discipline of criminology student starts with their respective homes. The environment plays a huge role in criminology students’ behavior and attitude. It shows in how they were their uniform, proper haircut, and also their behavior when wearing their uniform. The result reveals that the greatest number of respondents were both in 2nd year and 3rd year, and the lowest number of respondents were faculty members. The result showed that the respondents had agreed that they could adopt unusual traditions, adjust uncommon practices, and instruct new apprentices in terms of culture, as evidenced by the overall weighted mean rating of 2.91. Researchers concluded that there is a split belief between male and female respondents about instilling students’ discipline for criminology students regardless of their school year. However, their age and experience might cause them to have different views on the matter with regard to problems encountered; moreover, in different cultures, different practices are not a concern as long as the student is willing to adapt to new changes.